Automated well control using MPD approach - Birkeland, Trygve (University of Stavanger, Norway, 2010)
Master's thesis in Petroleum engineering The easy oil and gas is gone. Newly discovered fields follow the trend of being smaller and harder to reach, moving to increasingly remote locations with high temperatures. The huge fields of the past are maturing and depleting, which can lead to a narrower window between pore pressure and fracture pressure. Combining this with the recent decline in oil prices, the demand for lower drilling costs and more efficient drilling becomes evident. Managed Pressure Drilling (MPD) offers a solution to this by balancing the downhole pressure and reducing Non-Productive Time (NPT) while drilling. The last couple of years have seen a steady rise in application of this technology. Although similar to Underbalanced Drilling (UBD) in terms of equipment used, MPD does not welcome influxes to surface while drilling. It is, however, better equipped to deal with any resulting influx than a conventional drilling operation. A literary review of the various methods and applications of the technology is presented, along with the equipment needed and the drilling problems MPD seeks to negate. The main focus is on the Constant Bottomhole Pressure (CBHP) variation of MPD as this is planned for use on Kristin, an HPHT field in the Norwegian Sea. If successful, this would be the world’s first application of MPD on a floating drilling vessel in harsh conditions. Special emphasis is placed on well control, as well as detection and subsequent circulation of kicks. Kick simulations were performed in Drillbench© for a well drilled conventionally on Kristin in 2008, referred to as Well A. The simulation setup was based on 160 bar depletion in the Ile formation, while the Garn formation above was undepleted. The simulations showed that kicks from Garn of 1.6 m3 and above would fracture the Ile formation for low mud weights. Based on this, it is not recommended to drill conventionally on similar depleted wells, due to the narrow window between pore and fracture pressure. MPD is recommended as an ...